Plasma Assisted Preparation of CoPt/SiO2 Fischer‐Tropsch Catalysts: A Comparison of the Precursor Pre‐Thermal Treated Temperatures. Issue 2 (28th November 2018) - Liu, Chen; Liu, Hao; Wang, Bo; Hong, Jingping; Zhao, Fuzhen; Sun, Fenglou; Jin, Shiwei; Liu, Chengchao; Zhang, Yuhua; Li, Jinlin
Abstract: A series of amorphous silica supported Co‐based catalysts were prepared using traditional incipient wetness impregnation methods followed by thermal treatment at different temperatures. Glow discharge plasma effects on cobalt species in the forms of cobalt nitrate, mixture of cobalt nitrate and Co3 O4, and pure Co3 O4 were compared and investigated by various characterizations and Fischer‐Tropsch synthesis (FTS) tests. Plasma enhancing metal dispersion effect was mostly happened during the decomposition of cobalt nitrate in plasma field; when cobalt species was already in the form of Co3 O4, no apparent particle size change by plasma treatment was observed. Under the promotion of Pt, all the catalysts maintained at high reduction degree, thus the cobalt dispersion was almost linearly related to the number of active sites. The CoSi‐100D+P catalyst with both high cobalt dispersion and high cobalt reducibility, had the maximum number of active sites, and presented the highest FTS activity. Meanwhile, the product selectivity could also be affected by plasma treatment, hydrocarbons were shifted to lower carbon numbers. This effect could be observed even on the CoSi‐400C+P sample, in which the precursor was pre‐thermal treated at high temperature (400 °C), and cobalt species was already all transformed into Co3 O4 . Abstract : 1. Glow discharge plasma effects on cobalt species in different forms were investigated. 2. Cobalt dispersion enhancement was mostly occurred during the decomposition of cobalt nitrate by active species in plasma field. 3. Plasma treatment could modify the surface properties of catalysts and affect the product selectivity.